Visualisasi Data Penjualan PT XYZ Dengan Tableau - Sagaro, Ariya; Sutrisno, Tri; Lewenusa, Irvan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In a competitive business environment, Company XYZ faced challenges in efficiently managing and analyzing sales data. To address this issue, this study developed an interactive dashboard that simplifies data visualization through prototyping methods, using the Extract, Transform, and Load (ETL) process with Google Colab and Python, and final visualization using Tableau. The goal was to speed up and clarify the decision-making process by presenting sales data in various visual formats such as graphs, charts, and maps. The author faced several significant challenges including integrating inconsistent data from various sources, gaining a deep understanding of user needs, overcoming technological limitations, designing an intuitive user interface, and the necessity for comprehensive testing to ensure system reliability. As a result, this dashboard enhanced operational efficiency and data analysis quality at Company XYZ, enabling quicker responses to market dynamics and improving the company’s competitiveness. With this dashboard, Company XYZ has been able to minimize data analysis time while enhancing accuracy in their business and operational strategies.